Analyzing the Role of Spatial Planning Law in Promoting Social Justice and Environmental Protection for Vulnerable Urban Communities - Retno Eko Mardani; Ani Purwanti; Bagus Hermanto (Green Social: International Journal of Law and Civil Affairs, 2025)
Rapid urbanization, especially in developing countries, has worsened spatial inequality and environmental degradation, impacting vulnerable urban communities living in informal settlements with limited access to services and increased environmental risks. This study examines the role of spatial planning law in promoting social justice and environmental protection in urban areas, particularly for marginalized populations. While spatial planning laws have the potential to promote equity and sustainability, inconsistent enforcement and inadequate evaluation mechanisms reduce their effectiveness. Using a qualitative legal analysis approach, the research reviews statutory frameworks, urban planning documents, and case studies to assess the practical application of these laws. Findings show that integrating spatial planning laws with social justice and environmental sustainability principles can enhance the living conditions of vulnerable communities by ensuring equitable resource access and reducing exposure to environmental hazards. However, fragmented legal frameworks, weak enforcement, and a lack of participatory planning hinder their impact. Comparing with traditional urban planning, social justice-oriented spatial planning provides more sustainable outcomes by prioritizing equity and environmental protection. The study recommends policy reforms to strengthen law enforcement, encourage inclusive decision-making, and integrate social justice and sustainability into urban planning frameworks. Further research is needed to assess the long-term impacts and role of these laws in achieving equitable urban development.